Attendance and absence in reading the graphic: (picture drawing) - Mahdi, Nada Abudl Hadi (Al-Adab Journal, 2021)
The concept of attendance and absence is one of Derrida’s deconstructive arguments, because all procedures for the critical process of deconstruction are subject to the presence of functions and the absence of meaning. On this basis, the researcher determines the coordinates of her research tagged "Attendance and Absence in Reading the graphic picture" (Drawing). The first chapter - the methodological framework - includes the research problem, which was summarized by the question: What are the mechanisms of attendance and absence in reading the graphic picture? "The importance of the research is represented by the importance of the subject of artistic criticism as one of the trends of contemporary art education. As for the aim of the research, it is - revealing the mechanisms of attendance and absence in reading the graphic picture -. The second chapter - theoretical framework and previous studies - the first topic comes under the title - deconstruction as a contemporary critical trend - while the second topic is identified entitled - Reading the graphic picture. As for the third chapter - the research methodology and procedures - it comes by defining the descriptive analytical approach as being the closest to the current research requirements. The research, its sample and the research tool are identified. The fourth chapter deals with presenting the results, conclusions, recommendations, and proposals. In the end comes the list of sources.